An unusually high substitution rate in transplant-associated BK polyomavirus in vivo is further concentrated in HLA-C-bound viral peptides - Domingo-Calap, Pilar; Schubert, Benjamin; Joly, Mélanie; Solis, Morgane; Untrau, Meiggie; Carapito, Raphael; Georgel, Philippe; Caillard, Sophie; Fafi-Kremer, Samira; Paul, Nicodème; Kohlbacher, Oliver; González-Candelas, Fernando; et al. (PLOS Pathogens, 2018)
Author summary Little is known about the mechanisms of evolution and viral immune escape in double-stranded DNA (dsDNA) viruses. Here, we study the evolution of BK polyomavirus and observe the highest genomic evolutionary rate described so far for a dsDNA virus, in the range of RNA viruses, which usually evolve rapidly. Furthermore, the prediction of viral peptides to determine immune escape suggests a specific role of HLA-C in antiviral immunity. These findings are helpful for future advances in antiviral therapies and provide a step forward in our understanding of in vivo viral evolution in humans.